Implementation of rational emotive behavior therapy (rebt) to reduce the negative impact of introverted students - padillah, raup; Ramli, M. (International Journal of Applied Guidance and Counseling, 2023)
Students who have introverted personalities often experience difficulties when faced with situations that require them to carry out social interactions. This has an impact on their role in several lecture activities, especially in group assignments that require collaboration in the process. Based on research results, the negative impact of introverts is excessive worry, pessimism, lack of confidence, fear of opinions, and not daring to appear in public. This self-closing character makes it difficult for lecturers to develop their academic potential and achievements. One effort that can be made to reduce the negative impact of introverted students is Rational Emotive Behavior Therapy (REBT) counseling. This research is quasi-experimental, using non-equivalent pretest-posttest control group design. This research was conducted at PGRI Banyuwangi University, with the research subjects being students who fall into the introvert category. The sampling technique is called purposive sampling. The instruments used in this study include observation, interviews, and questionnaires. The instruments used in this study include observation, interviews, and questionnaires. Based on the results of data processing using SPSS, the results of group counseling treatment with the REBT (rational emotive behavior therapy) approach for subjects indicated to be introverts in this study stated that t-count = 20,294 with a significance level of 0.05, so t-table = 2,201. Based on these findings, it is possible to conclude that the t count > the t table, or that 20,294 > 2,201. Thus, it can be concluded that group counseling with the REBT approach can reduce the negative impact of introverts on counseling students at PGRI Banyuwangi University. This results shows that group counseling with the REBT approach is able to reduce the negative impact of introverts on students.